2021
DOI: 10.1038/s42003-021-02738-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrocorticography reveals thalamic control of cortical dynamics following traumatic brain injury

Abstract: The return of consciousness after traumatic brain injury (TBI) is associated with restoring complex cortical dynamics; however, it is unclear what interactions govern these complex dynamics. Here, we set out to uncover the mechanism underlying the return of consciousness by measuring local field potentials (LFP) using invasive electrophysiological recordings in patients recovering from TBI. We found that injury to the thalamus, and its efferent projections, on MRI were associated with repetitive and low comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…We believe that those drivers might be linked both to the regions participating in the RAS system (Intralaminar Thalamus, Raphe Nuclei, and Locus Coeruleus) [4, 16] and to the dorsal nuclei of the thalamus that are implicated in the relay of sensory information and have also been tightly linked to the generation of oscillatory behavior in the cortex in slow waves [6366]. This would support the view of the thalamus as a driver and controller of cortical dynamics [6, 25, 6769].…”
Section: Discussionmentioning
confidence: 82%
“…We believe that those drivers might be linked both to the regions participating in the RAS system (Intralaminar Thalamus, Raphe Nuclei, and Locus Coeruleus) [4, 16] and to the dorsal nuclei of the thalamus that are implicated in the relay of sensory information and have also been tightly linked to the generation of oscillatory behavior in the cortex in slow waves [6366]. This would support the view of the thalamus as a driver and controller of cortical dynamics [6, 25, 6769].…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, phase- and amplitude-coupling patterns may partly reflect different neuronal mechanisms ( Siems and Siegel, 2020 ; Duclos et al, 2021 ). In general, the presence of high-frequency oscillations, corticocortical and thalamocortical connections (structural and functional) is associated with higher levels of consciousness ( Mofakham et al, 2021 ; Oberto et al, 2022 ). Delta activity and synchronization appear to be higher when the cortical arousal is at a lower level ( Sitt et al, 2014 ; Frohlich et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… 14 More recently, our work has demonstrated that DTI can be used to assess the structural integrity of thalamocortical projections and that preservation of these connections is associated with earlier command following after severe TBI. 33 - 35 Therefore, structural imaging methods can assess injuries to areas critical to consciousness and provide valuable prognostic information.…”
Section: Neuroimagingmentioning
confidence: 99%
“…Our observations in patients with severe TBI and in silico have demonstrated that thalamic injury results in dysfunctional cortical networks with simplistic and repetitive characteristics, supporting the idea that thalamic input is crucial for the content of consciousness. 33 …”
Section: Areas Of Controversymentioning
confidence: 99%